Photocatalytic Active Coatings for Lignin Degradation in a Continuous Packed Bed Reactor - Colin Awungacha Lekelefac; Johannes Hild; Peter Czermak; Michael Herrenbauer (International Journal of Photoenergy)
The synthesis of immobilized catalyst on porous glass support material via the sol-gel route is reported. TiO2-P25-SiO2 + Pt, TiO2-P25-SiO2, TiOSO4_30.6 wt%, and ZnO + TiO2-P25-SiO2 catalysts were synthesized and a comparative study is done regarding morphology of coatings, degradation rates, reaction rates, dissolved carbon (DC), formation of peaks, and fluorescence of products formed from the photocatalytic degradation of lignin sulfonate obtained from a local paper plant. Through simultaneous reaction-extraction pathways applying dialysis filtration and highly porous polystyrene divinylbenzene adsorbent resin (HR-P) for solid phase extraction (SPE), an attempt has been made to isolate smaller molecules produced from photocatalytic degradation. Moreover relatively high lignin sulfonate (0.5 g/L) concentrations are used in the reactions. UV-Vis spectroscopy revealed a faster reduction in the concentration values for the aliphatic moiety compared to the aromatic moiety. Peaks were observed by both fluorescence spectroscopy and HPLC suggesting the production of new substances and fluorophores.